Spatial and depth patterns of reef fish assemblages in Pulau Tenggol, Malaysia and their links to benthic composition - RAHMAN SYAFRUDDIN; MOHMAD FUAD NUR QAMARINA; CHE DIN MOHD SAFUAN; YUSRI YUSUF; AMINUDIN MUHAMMAD AFIQ-FIRDAUS; ZAINUDIN BACHOK (Society for Indonesian Biodiversity, 2026)
Abstract. Syafruddin R, Qamarina MFN, Safuan CDM, Yusuf Y, Afiq-Firdaus AM, Bachok Z. 2026. Spatial and depth patterns of reef fish assemblages in Pulau Tenggol, Malaysia and their links to benthic composition. Biodiversitas 27 (1): d270148. https://doi.org/10.13057/biodiv/d270148. A total of 142 reef fish species (71 genera, 33 families) were recorded at Pulau Tenggol in the South China Sea, Peninsular Malaysia, based on surveys conducted in May 2024 across five stations and three depth strata (5, 10, and 15 m), yielding 12 station-depth transects. Fish assemblages were surveyed using belt transects, while major benthic categories and Hard coral growth-forms composition were quantified using Coral Video Transects and analyzed with Coral Point Count with Excel extensions (CPCe). Fish indices, including fish density, species richness, Shannon diversity, Simpson diversity, and Pielou’s evenness, showed no significant differences among stations or depths (Kruskal-Wallis test, p>0.05), whereas species composition differed significantly across both spatial and depth gradients (PERMANOVA, p>0.05). Major benthic categories and hard coral growth-forms did not differ significantly with depth (p>0.05) but showed significant variation among stations (p>0.05). Mantel tests indicated that fish assemblage structure was significantly associated with hard coral growth-forms (p≤0.05), while no significant correlation was detected with major benthic categories (p>0.05). Fish density was positively correlated with Acropora staghorn/branching growth-forms (ρ: 0.783, p: 0.004, FDR: 0.047; partial ρ: 0.769, p: 0.006, FDR: 0.073) and negatively correlated with encrusting corals (ρ: -0.790, p: 0.004, FDR: 0.047; partial ρ: -0.775, p: 0.005, FDR: 0.073). Healthy hard coral cover was strongly associated with obligate corallivores (ρ: 0.757, p: 0.004, FDR: 0.015; partial ρ: 0.716, p: 0.013, FDR: 0.017) and Chaetodontidae (ρ: 0.669, p: 0.017, FDR: 0.035; partial ρ: 0.616, p: 0.044, FDR: 0.027). Overall, coral health and growth-form complexity were stronger predictors of reef fish assemblage structure than major benthic categories.